Comparison of children's inheritance laws outside marriage in Indonesia with several other countries - Septiana, Dewi; Mujtahidin, Syamsul; Taufik, Zahratul'ain (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The rights of a child, both legitimate children and children outside of marriage, should remain protected and prioritized. However, in reality there are still many parents who do not recognize children who have been born outside of marriage. Especially a biological father. This study discusses how the rights of a child outside of marriage and what the legal consequences are obtained. This study concluded that the rights of children out of wedlock in accordance with the provisions of civil law, Islamic law, and customary law states that their rights can be obtained if a child can prove that he is a legitimate descendant of his biological father. The way that can be taken can be in the form of proving through DNA tests and getting recognition from his biological father.